G503(P) Initial results from a pilot enabling frontline staff to identify human factors in patient safety incidents on a paediatric intensive care unit. (27th April 2016) - MacGloin, H; Knight, P; Haxby, E; Mortimer, P; Lofton, L; Lane, M; Desai, A; Burmester, M
Abstract : Background and aims: Human factors (HF) is the science of human performance within a given system. 1 It was adopted by healthcare from safety critical industries to improve patient safety. HF training is recommended by the General Medical Council (GMC), World Health Organisation and Royal Colleges. 2 3 Despite the importance of HF to patient safety, there is a relative paucity of research on how to incorporate HF perspective within existing patient safety reporting systems such as Datix. Aims: To analyse the contribution of HF within Datix reports submitted from the Paediatric Intensive Care Unit. To enable a HF perspective in patient safety incidents (PSI) within the paediatric directorate. Methods: PICU Datix submitted between 1.4.2007–1.4.2015 were analysed according to HF categories which were devised according to "Implementing Human Factors in Healthcare: How to Guide". 4 A drop-down menu on Datix was developed to enable staff to choose a HF at the time of reporting. The new system became live from 1.10.2015. The effect of the change on reports submitted by PICU between 1.10.2015–1.12.2015 was analysed. This work was registered as a quality improvement initiative. Results: 1946 PICU Datix were submitted from April 2007–April 2015. 329(20.3%) reported HF. Communication (10.4%, n = 203), was the most commonly cited HF. 127 PICU Datix were submitted between 1.10.2015–1.12.2015. 48 (37.8%) attributed a contributory HF, most 19 (15%) cited communication. Conclusion: Simple changes to existing safety tools can enable a HF perspective to overcome wrong assumptions about error causation. The relevance of HF is still not fully embraced within reports but within 2 months, HF reporting has increased since the change in reporting system and there has been subsequent trust-wide implementation of HF within Datix. Further research is required as we strive to improve the safety culture of teams and organisations and a human factors perspective will feature increasingly as healthcare's socio-technically complex system is better understood. References: DoHclass="RefAuthor"> Human Factors Reference Group Interim Report, National Quality Board, March 2012 GMC Academy of Medical Royal Colleges July 2015 "Developing a framework for generic professional capabilities" A public consultation WHO Patient Safety Curriculum Guide: Multi-professional edition 2011 Carthey, J Patient Safety First: The "How to Guide" for Implementing Human Factors in Healthcare Version 1 2009